SOLIDARITAS SOSIAL MASYARAKAT DALAM TRADISI TULAK BALA DI DESA MESJID TUHA KECAMATAN MEUREUBO KABUPATEN ACEH BARAT - yana, rahmah husna (Jurnal Society : Pengamat Perubahan Sosial, 2023)
Tulak bala is a traditional practice in Mesjid Tuha Village, Meureubo Sub-district, West Aceh, aimed at averting disasters and seeking protection. This research explores the transformation of social solidarity within the tulak bala tradition, using Emile Durkheim’s perspective. Employing a descriptive qualitative approach, data were collected through observation, interviews, and documentation involving key informants. The findings reveal a shift in the form of solidarity from mechanical to a more organic type. Previously, the tradition emphasized strong kinship bonds, shared beliefs, and mutual cooperation. However, with ongoing social changes, solidarity has weakened. Ritual aspects have also changed, including modifications in the types and quantities of offerings and reduced community involvement. Participation has shifted from active and collective to more passive and individual. The tradition, once a symbol of communal unity, now reflects broader societal transformations, where rituals have become more complex but less inclusive. This study highlights how modernization and shifting social structures influence local cultural practices and community solidarity.